Plan kont - zakładowy czy uniwersalny? - Koczar, Joanna (Company's Chart of Accounts - Created or Uniform, 2005)
Company's accounting policies should find a reflection in documentation and in company's chart of accounts as well. There is a tendency in Polish economic practice to assume the company's chart of the accounts as uniform pattern, which doesn't include the specific characteristic of individual entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 26-28